Influence of Compliant Joints in Four-Legged Robots - Spadaro, Francesco Tracuzzi; Muscolo, Giovanni Gerardo (Frontiers in Mechanical Engineering, 2020)
Legged animals are capable of rapid movements, are efficient from the energy point of view, and are able to adapt their gaits to environmental conditions. Motions like walking, trotting, galloping, and jumping, are difficult to evaluate and replicate due to their being consequences of complex interactions of different systems (such as the musculoskeletal system and the central and peripheral nervous systems, including also the influence of the environment). In this paper, we analyzed the behavior of a four-legged robot constituted by one active DOF in each leg (using commercial servomotors) and one passive DOF in each knee and in the spine (using springs). Our objective was to increase the motion performances of the robot by varying the stiffness of the springs. The results obtained from the simulation underline how the stiffness of the spine influences the performance of the robot by increasing the speed and reducing the energy required by the servomotors.